Assessing maize water requirements in the context of climate change uncertainties over southern Africa - Hachigonta, Sepo Promise (Department of Environmental and Geographical Science, 2014)
Climate change studies are subject to high uncertainties partly resulting from data reliability. This study investigates the challenges of using statistical downscaled climate data to examine the likely impacts of climate change on maize growth in southern Africa in the context of these uncertainties.